Dental and Oral Health Behaviour of Social and Political Sciences Student - Deshinta, Aulia; Selvia, Mega; W, Levina Gita; F.M, Ekky Nur; Safira V, Yasmin; N, Nadiyya Nurul; Azizah, Nur; Kusumo, Aryo Dwipo (International Journal of Psychosocial Rehabilitation, 2020)
Purpose: To find out the behaviour of Social And Political Sciences students from Universitas Airlangga on dental and oral health. Method: This study was a quantitative descriptive research. Information was obtained through an online questionnaire about behaviours related to dental and oral health. Results: The behaviour of Social And Political Sciences female students related to maintaining oral health was better (95.8%) compared to Social And Political Sciences students (90.9%). There was 94.9% of Social And Political Sciences students at Universitas Airlangga have good behaviour towards oral health with an average score of 12.4% (score> 10) while 5.1% of other students have an average score of 8.3 (score